2012
DOI: 10.1074/jbc.m112.345215
|View full text |Cite
|
Sign up to set email alerts
|

Nectin-1 Binds and Signals through the Fibroblast Growth Factor Receptor

Abstract: Background: Nectin-1 is a cell-adhesion molecule important for the formation of synapses. Results: The third Ig module of nectin-1 (nectin-1 Ig3) induces neuronal differentiation and promotes neuronal survival through a direct interaction with FGF receptor. Conclusion: FGF receptor is a downstream signaling partner of nectin-1. Significance: This mechanism of nectin-1 signaling is crucial for understanding its neuritogenic and survival promoting effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0
4

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 51 publications
(60 reference statements)
0
24
0
4
Order By: Relevance
“…Neuronal nectin-1 may bind functionally to nectin-1 to itself, to nectin-3 or to the fibroblast growth factor receptor (FGFR) [4], [55]. Nectin-3 and nectin-1 share a binding site on the first Immunoglobulin-like domain (V-domain) of nectin-1 [56], [57] and promote cellular and synaptic adhesion.…”
Section: Discussionmentioning
confidence: 99%
“…Neuronal nectin-1 may bind functionally to nectin-1 to itself, to nectin-3 or to the fibroblast growth factor receptor (FGFR) [4], [55]. Nectin-3 and nectin-1 share a binding site on the first Immunoglobulin-like domain (V-domain) of nectin-1 [56], [57] and promote cellular and synaptic adhesion.…”
Section: Discussionmentioning
confidence: 99%
“…The oxifin1 peptide derived from CD200 mimicked its neuritogenic and survival-promoting effects [96]. Proteins of the cell adhesion molecule (CAM) family, such as nectin-1, can also bind and activate FGF receptors [97]. CAMs signal through FGF receptors by trans-homophilic/heterophilic interactions of CAMs on opposite cells.…”
Section: Targeting the Fgf Systemmentioning
confidence: 99%
“…Nectin-1 is prominently expressed in brain, including the hippocampus. Furthermore, nectide is a peptide derived from nectin-1 which can mimic its effects, including those on cell survival [97]. …”
Section: Targeting the Fgf Systemmentioning
confidence: 99%
“…Most of these studies were done in transfected cell lines overexpressing these proteins, and it still remains unknown whether these interactions are direct or indirect. The direct interaction was reported only between nectin-1 and the FGF receptor (47). In this report, it was shown that the third Ig module of nectin-1 directly interacts with the FGF receptor as estimated by surface plasmon resonance.…”
Section: Discussionmentioning
confidence: 73%
“…Nectin-4 serves as the entry receptor for measles virus (66,67). In addition, nectin-1 and nectin-3 cis-interact with the FGF receptor and the PDGF receptor, respectively (42,47). Therefore, the novel cell adhesion apparatus identified here may also serve as a platform for cellular signaling and play physiological and pathological roles not only in the mammary gland but also in other organs.…”
Section: Discussionmentioning
confidence: 85%